2020
DOI: 10.5586/asbp.8939
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Araceae and the Diversity of Life Forms

Abstract: This paper discusses the family Araceae, emphasizing its worldwide distribution and the diversity of morphological and ecological characteristics of the family that have enabled it to reach such a prominent position with diverse habitats. Few families of its size have come to inhabit such a diverse spectrum of habits and biomes. The family has important habit forms and growth structures that have enabled such distributional patterns. The very broad spectrum of life forms it demonstrates is one of the main char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 112 publications
0
11
0
2
Order By: Relevance
“…Tavolo, which has been naturalized in Madagascar, is typically found in tropical forest openings and grasslands (Missouri Botanical Gardens, n.d.). Via, a wild aroid native to Madagascar and South Africa (Croat and Ortiz, 2020), grows in marshy areas. Both are used as medicinal plants: tavolo to treat malnutrition, and via to aid in placental evacuation, alleviate hip problems (Razafindraibe et al, 2013), treat burns and wounds (Rabearivony et al, 2015), and as a remedy against venomous bites (USDA Bureau of Plant Industry, 1919).…”
Section: Forager-farmers Of Madagascarmentioning
confidence: 99%
“…Tavolo, which has been naturalized in Madagascar, is typically found in tropical forest openings and grasslands (Missouri Botanical Gardens, n.d.). Via, a wild aroid native to Madagascar and South Africa (Croat and Ortiz, 2020), grows in marshy areas. Both are used as medicinal plants: tavolo to treat malnutrition, and via to aid in placental evacuation, alleviate hip problems (Razafindraibe et al, 2013), treat burns and wounds (Rabearivony et al, 2015), and as a remedy against venomous bites (USDA Bureau of Plant Industry, 1919).…”
Section: Forager-farmers Of Madagascarmentioning
confidence: 99%
“…According to Acebey et al (2010), Araceae are often found in moist lowland and montane forests, but they can also be found in seasonally dry forest habitats. Araceae has a wide diversity of habitats; therefore, the species diversity is high (Croat and Ortiz, 2020). The Fabaceae family has a wide distribution in almost all parts of the world; its good adaptability makes species of the Fabaceae family grow wild, especially on the tropical island of Java (Mountara et al, 2021).…”
Section: Vascular Plants In Somopuro Cavementioning
confidence: 99%
“…Subsequently, its insular nature and complex geological history have resulted in the evolution of globally diverse fauna and flora (von Rintelen 2017). Araceae (aroids) is a globally distributed plant family with 144 genera and 3,645 species (Croat et al 2020). Aroid plants include submerged aquatic or free-floating plants, terrestrial (sometimes tuberous) plants, and epiphytes (Nugroho 2008).…”
Section: Introductionmentioning
confidence: 99%